Uncovering undiagnosed liver disease: prevalence and opportunity for intervention in a population attending colonoscopy - Laura J Neilson; Colin J Rees; Stuart McPherson; R Bevan; Salil Singh; A Verma; Mark Hull; Sara Koo; J Greenaway; Steven Rushton; Robert Hart; Clair Gabriel; et al. (BMJ Open Gastroenterology)
Objective Due to high rates of obesity and alcohol consumption, the prevalence of fatty liver disease is increasing. There is no widely adopted approach to proactively screen for liver disease in the community. We aimed to assess the burden of potentially undiagnosed liver disease in individuals attending for colonoscopy to develop a pathway to identify and manage individuals with undiagnosed liver disease.Design The OSCAR Study was a cross-sectional study recruiting patients attending for colonoscopy. Patients’ metabolic and liver risk factors were measured. The prevalence of undiagnosed significant fatty liver disease was measured using the Fatty Liver Index (FLI) and Fibrosis-4 score (FIB-4).Results 1429 patients (mean age 59±14 years; 48.8% men) were recruited. 73.3% were overweight/obese, 12.7% had diabetes and 17.9% had metabolic syndrome. 19% were consuming more than recommenced alcohol levels (<14 units/week) and 41% had an AUDIT-C score ≥5. After excluding those with known liver disease, 43.2% of the cohort had a high FLI (high likelihood of fatty liver). 5.3% of these had a high FIB-4 score (>2.67, high probability of advanced fibrosis) and 90% of these were previously undiagnosed. 818 patients had a predicted 10-year cardiovascular event risk of ≥10%, however only 377 (46.1%) were on statin therapy.Conclusion High levels of obesity, metabolic dysfunction and undiagnosed fatty liver disease were found in individuals attending for colonoscopy. Clinical encounters in the endoscopy unit may represent an opportunity to risk assess for liver and metabolic disease and provide an environment to develop targeted interventions.